State-led housing development in Brazil and India: a machinery for enabling strategy?. Issue 4 (2nd October 2019) - Sengupta, Urmi
Abstract: Housing has been one of the defining issues of our times. Enabling strategies were implemented to address the housing challenges over the past decade with limited success. In recent years, there has been a resurgence of government-led large-scale programmes to provide low-income housing. New networks of collaborations have created new rules and shifted boundaries to achieve scale. In India, Pradhanmantri Awas Yojana (PMAY) aims to build 20 million new units by 2022. Likewise in Brazil, Minha Casa Minha Vida (MCMV) was launched to deliver millions of affordable homes. This paper argues that the emergence of state-led housing means the value of enabling has not been supplanted but supplemented, as the shift does not herald the end of enabling strategy but a renewed commitment to the expansion of enabling principles where the state is an active agent. The state-led housing development is creating and formalising new areas of market engagement, and is far less radical and transformative than is assumed. State housing programmes such as MCMV and PMAY are inevitability highly profitable transactions, advantageous to the economy and housing markets and come at a point when profiteering and resource-extracting neoliberalism is at its zenith.